ENT 530 Case Study: Nasi Lemak Che Ta / Nurfarzana Liyana Nawawi ... [et al.] - Nawawi, Nurfarzana Liyana; Mohammad, Nor'ai; Mohd Shah, Alia Natasha; Ghazali, Nur Athirah; Nor Azmi, Nor Alia Aqilah; Mohd Aris, Nur Syuhada; Mohd Nasir, Nur Adila; Saffar, Nur Aqila Najwa; Azali, Nurul Nabilla (2021)
The business that have been chosen by Che Ta is Nasi Lemak which is a good choice for she to start her business because we as Malaysia really wanted for variety of spicy food. She really follow the Malaysian taste and she know what society want and need. What we can summarised from her business, we all know that Malaysia preferred buying Nasi Lemak instead of going to big restaurant that can cost many money and can waste their time just by waiting for the food. In this era, most people prefer to buy a food that can be done faster and the food that make them feel full. Che Ta have their own business strategy which is she have her own objective, mission and vision. She also make her own marketing strategy which it include product strategy, price strategy and distribution strategy so that her business can grow more bigger.